(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
In the article, during the Second World War, the issues of population representatives, children and children’s homes, who were transferred to Uzbekistan, including Andijan, Namangan and Fergana regions from the frontline regions, and the care shown to them by the population, are covered based on primary sources.